1995
DOI: 10.1093/ajcn/61.5.1043
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of palmolein and olive oil: effects on plasma lipids and vitamin E in young adults

Abstract: Twenty-one healthy normocholesterolemic young adults, men and women, completed a randomized 30-d/30-d crossover comparison of the effect of palmolein and olive oil on plasma lipids. The subjects were free-living volunteers who changed to low-fat diets to which one of the test oils was added (used as a spread, for baking, or for frying) in turn. Complete food records were kept throughout: the test oils were compared at 17% of total dietary energy. Under the conditions of this experiment plasma total and low-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 55 publications
10
64
1
2
Order By: Relevance
“…Palmolein contains more saturated and less MUFA (Table 3). We found that total and LDL cholesterols were lower on canola oil than on palmolein (Truswell et al, 1992) and on higholeic sun¯ower oil than on palmolein (Choudhury et al, 1997) as predicted by the Keys et al (1957) equation, but they were not lower on olive oil than on palmolein (Choudhury et al, 1995). HDL cholesterols averaged 0.10 mmol/l higher on palmolein than on each of the three MUFA oils.…”
mentioning
confidence: 67%
“…Palmolein contains more saturated and less MUFA (Table 3). We found that total and LDL cholesterols were lower on canola oil than on palmolein (Truswell et al, 1992) and on higholeic sun¯ower oil than on palmolein (Choudhury et al, 1997) as predicted by the Keys et al (1957) equation, but they were not lower on olive oil than on palmolein (Choudhury et al, 1995). HDL cholesterols averaged 0.10 mmol/l higher on palmolein than on each of the three MUFA oils.…”
mentioning
confidence: 67%
“…Whether the effect of regioselective distribution of these fatty acids can be extended to other fatty acids deserves particular attention. Choudhury et al, (1995) show that synthetic fats have fatty acids randomly attached to the glycerol molecule. This contrasts with natural fats, which have a specific fatty acid distribution and the positions of these fatty acids along the glycerol molecule can modulate the effect of different fats on cholesterol metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…This was ®rst hypothesized by Threfall (1971). In a study comparing palmolein Lipemia from palm and oleic acid-rich sun¯ower oils C Cuesta et al and olive oil, Choudhury et al (1995) reported that tocotrienols wee barely detectable in plasma. Therefore, in the present study, the plasma a-tocopherol concentrations seen following the palmolein period could be due to the conversion of tocotrienols to a-tocopherols.…”
Section: Serum Lipid Lipoprotein and Apo Concentrationsmentioning
confidence: 99%
“…This study represents a ®rst test of the hypothesis that 16:0 can be hypercholesterolemic compared to 18:1 in postmenopausal women with initially high TC and LDL-C values and with high intakes of dietary cholesterol (b 300 mgad). In addition, the peroxidative status of plasma and LDL at the end of each dietary period was investigated since both oils are rich in antioxidants (Choudhury et al, 1995) but palmolein was particularly rich in tocotrienols and showed a higher saturation index.…”
Section: Introductionmentioning
confidence: 99%